Information quality for mobile application development to assists pilgrims: a theoretical model - Arbaaeen, Ammar; Shah, Asadullah (IEEE, 2023)
Providing users with quality information is essential for the success of mobile application development. Hajj mobile application development is complex due to user satisfaction level, age and cultural difference, lack of interactivity, and the efficiency of the Hajj mobile application. Thus, in order to solve these problems, we intent to examine the effect of mobile information quality as the independent variables: a) content, b) contextual, and c) interaction on the effectiveness of the mobile application as the dependent variables: a) usability, and b) interactivity among user with different cultural and age range. This study identifies essential information quality dimensions which reflect to the characteristics of mobile application development in order to increase pilgrim satisfaction. There are total of 180 users selected randomly from pilgrims to validate the hypothesized model. The results show that some information quality factors are more essential than others in increasing user satisfaction and reflect the effective characteristics in mobile application development.